Composite "graphene nanoplatelets - fluorine-containing polyamide": synthesis, properties and quantum-chemical simulation of electroconductivity - Kachkovsky, A.D.; Pavlenko, E.L.; Sheludko, E.V.; Kulish, N.P.; Dmitrenko, O.P.; Sendyuk, V.A.; Smertenko, P.S.; Kremenitsky, V.V.; Tarasyuk, O.P.; Rogalsky, S.P. (Functional Materials, 2019)
Considered in the article is the basic possibility of increasing of electric conductivity of thermostable fluorine-containing aromatic polyamide by its doping with graphene platelets. The raised concentration of a conducting graphene phase (78 wt.%) in the top layer (~ 50 μm) of the film composite is established. The microstructure of cross-section of the film and topography of its surface are studied by SEM and AFM. Corresponding volt-ampere characteristics are resulted. Carried out here are quantum-chemical calculations of model system &qout;a polyamide fragment + graphene strip&qout;: localization of boundary and close molecular orbitals in the composite and also distribution of spin density of the composite in electric field. Conductivity of the composite is explained within the framework of stacking interaction between π-systems of the polymer and graphene.